Unique Relationships Between Autistic Traits and Visual, Auditory, and Tactile Sensory Thresholds in Typically Developing Adults. (April 2020) - Yaguchi, Ayako; Hidaka, Souta
Autism spectrum disorder (ASD) refers to neurodevelopmental disorders characterized by symptoms such as social deficits and restricted interests and behavior. Several studies have investigated specific sensory processing in relation to ASD traits. However, findings appear to be inconsistent and inconclusive because of variation in ASD traits among participants and differences in the tasks adopted. In this study, we investigated relationships between sensory thresholds in visual, auditory, and tactile modalities and various ASD traits to account for individual variability of traits in typically developing adults using the same experimental tasks. We estimated detection and discrimination thresholds for brightness, sound pressure, and vibrotactile stimulus strength. We also estimated the degree of ASD traits in each participant with a questionnaire. We found that higher tactile detection and visual discrimination thresholds were related to ASD traits in difficulty of communication. A lower tactile discrimination threshold and higher visual detection threshold was also related to the ASD trait of strong focus of attention. These findings suggest the existence of unique relationships between particular low-level sensory processing and specific ASD traits, indicating that irregularities in sensory processing may underlie variation in ASD traits.